Secukinumab in psoriasis: randomized, controlled phase 3 trial results assessing the potential to improve treatment response in partial responders (STATURE). (16th May 2015) - Thaçi, D.; Humeniuk, J.; Frambach, Y.; Bissonnette, R.; Goodman, J.J.; Shevade, S.; Gong, Y.; Papavassilis, C.; ,
Summary: Background: Secukinumab, an anti‐interleukin‐17A monoclonal antibody, has demonstrated rapid and sustained efficacy in phase 3 psoriasis trials. Objectives: To examine whether partial responders could achieve improved responses with intravenous (IV) secukinumab vs. the same or a higher subcutaneous (SC) dose. Methods: Forty‐three participants with moderate‐to‐severe psoriasis and partial response [Psoriasis Area and Severity Index (PASI) score improvement of ≥ 50% but < 75%] after 12 weeks of 300 or 150 mg SC secukinumab therapy were randomized 1 : 1 to secukinumab 10 mg kg −1 IV (baseline, weeks 2 and 4, respectively) or secukinumab 300 mg SC (baseline, week 4). All participants subsequently received secukinumab 300 mg SC every 4 weeks (weeks 8–36). Co‐primary end points were PASI 75 and Investigator's Global Assessment [2011 modified version (IGA mod 2011)] 0/1 response rates at week 8 (IV vs. SC). Results: Higher IGA mod 2011 0/1 response rates (66·7% vs. 33·3%; P  = 0·03) and a trend towards higher PASI 75 response rates (90·5% vs. 66·7%; P  = 0·06) were observed with secukinumab IV vs. SC at week 8. The primary objective was not met, as the difference was not significant for both co‐primary end points. Improved responses in both groups were maintained at week 40 in most participants. Safety profiles for IV and SC secukinumab were similar. The trial was underpowered owing to its small sample size. Conclusions: Improved response may be attained in patients with psoriasis achieving partial response after 12 weeks of SC secukinumab treatment by continued dosing with 300 mg SC or treatment with higher doses. Abstract : What's already known about this topic? Secukinumab has demonstrated rapid, strong and sustained efficacy in treating moderate‐to‐severe psoriasis [˜70–75% Psoriasis Area and Severity Index (PASI) 90 achievement by week 16]. What does this study add? The present trial suggests that responses to secukinumab in participants who are partial responders (PASI improvement ≥ 50% but < 75%) after 12 weeks of subcutaneous (SC) therapy may be improved by continued dosing with 300 mg SC or treatment with higher doses [short‐term intravenous secukinumab or a higher SC dose (300 vs. 150 mg)].